Origins of Parkinson’s Disease in Brain Development: Insights From Early and Persistent Effects of LRRK2-G2019S on Striatal Circuits - Huntley, George W.; Benson, Deanna L. (Frontiers in Neuroscience, 2020)
Late-onset Parkinson's disease (PD) is dominated clinically and experimentally by a focus on dopamine neuron degeneration and ensuing motor system abnormalities. There are, additionally, a number of non-motor symptoms--including cognitive and psychiatric--that can appear much earlier in the course of the disease and also significantly impair quality of life. The neurobiology of such cognitive and psychiatric non-motor symptoms is poorly understood. The recognition of genetic forms of late-onset PD, which are clinically similar to idiopathic forms in both motor and non-motor symptoms, raises the perspective that brain cells and circuits--and the behaviors they support--differ in significant ways from normal by virtue of the fact that these mutations are carried throughout life, including especially early developmental critical periods where circuit structure and function is particularly susceptible to the influence of experience-dependent activity. In this focused review, we support this central thesis by highlighting studies of LRRK2-G2019S mouse models. We describe work that shows that in G2019S mutants, corticostriatal activity and plasticity are abnormal by P21, the end of a period of excitatory synaptogenesis in striatum. Moreover, by young adulthood, impaired striatal plasticity likely underlies altered and variable performance by mutant mice in validated tasks that test for depression-like and anhedonia-like behaviors. Mechanistically, deficits in synapse and behavioral plasticity may be unified by a mutation-linked defect in AMPAR subunit trafficking, which in turn may reflect impairment in the function of the Rab family of GTPases, a major target of LRRK2 phosphorylation. These findings underscore the need to better understand how PD-related mutant proteins influence brain structure and function during an extended period of brain development, and offer new clues for future therapeutic strategies to target non-motor cognitive or psychiatric symptoms of PD.